PONDOK ‘S WORDS TRACE IN THE WRITING OF UNSIQ STUDENTS - puji - laksono (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2019)
ABSTRACT The purpose of this study is to explain the interference of the pondok’s words in the composition written by the first semester students of English department of UNSIQ Wonosobo. There are ten students who can fulfil the required criteria to be the subjects of research. The reason for choosing them is because they have not received extensive writing material. This research is a descriptive qualitative research. Data are collected by observing the compositions made by students. Data are analyzed using comparative analysis. The research findings are that all students studied still used pondok’s words their English compositions. Keywords: pondok, interference, mother tongue